Macro mobility scheme in NEMO to support seamless handoff - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Mahmoud, Omer; Saeed, Rashid A. (2012)
In order for the mobile networks to stay connected to the Internet, Network Mobility (NEMO) is involved with the management of the different types of movements by mobile routers during rapid changes of the Point of Attachment (PoA). Accordingly to achieve seamless handoff with lower delay and packet loss in NEMO environment, it is very important to get better performance of mobility management protocol. As the main idea of Network Mobility Basic Support Protocol (NEMO BSP) is to create bi-directional tunnel between the Serving Mobile Routers (SMR) with its Home Agent (HA) and perform the handoff after complete layer 2 switching. Therefore, it should limit frequent registrations of Mobile Network Nodes (MNNs) with their HAs. Furthermore, creating bi-directional tunnel between MR and its HA for all communications makes sub-optimal problem, in which all the packets are tunneled and encapsulated via HA of the Serving MR. This increases handoff delay, packet loss and disconnections probability. To overcome handoff related problems, the Fast Hierarchical Mobile IPv6 (FHMIPv6) works as a solution for host mobility. However, in nested NEMO environment applying improved FHMIPv6 mechanism is a challenging task since consideration has to be given to both MR and its MNNs as well. This paper proposed macro mobility scheme in order to achieve seamless handoff through modification of signaling messages. Additionally, location update cost is calculated and compared with NEMO BSP via analytical approach. The analytical result shows that the location update cost for the proposed scheme is about 69 % less than that of NEMO-BSP.